Vestiging van selkulture van Lycopersicon esculentum cv. Stevens - De Villiers, R. P.(Roelof Pieter) (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (M. Sc.) -- Universiteit van Stellenbosch, 1988.